SAT0507 Detection of Novel Cerebral Microvessel Lesions in Patients with Neuropsychiatric Systemic Lupus Erythematosus by 7Tesla MRI. (23rd January 2014) - Sasaki, N.; Murata, O.; Ninomiya, Y.; Hosoya, Y.; Suzuki, N.; Koizumi, R.; Nakamura, Y.; Kobayashi, H.; Yamauchi, K.; Sasaki, M.
Abstract : Background: The cerebral microvascular lesions of patients with neuropsychiatric systemic lupus erythematosus (NPSLE) have not been fully elucidated. The 7Tesla MR scanner has high image resolution and can be expected to detect cerebral microvascular lesions that have never before been visible. Objectives: We examined the cerebral microvascular lesions of NPSLE using a 7Tesla MR scanner. Methods: We studied 15 patient (5 NPSLE (three, acute phase; two, past history); 10, non-NPSLE). MRI was performed using a 1.5Tesla MR scanner and 7Tesla MR scanner (T1-weighted imaging(T1WI), T2-weighted imaging(T2WI), diffusion-weighted imaging(DWI), magnetic resonance angiography). Two radiologists performed the interpretation without clinical information. Diagnosis of NPSLE was determined by a neurologist, psychiatrist and rheumatologist. Results: Examination by the 7Tesla MRI revealed cerebral microvascular lesions in four of five NPSLE patients (acute phase, three; past history, one). These findings were not detected in any of the patients with non-NP SLE. The cerebral microvascular lesions were found around the central sulcus especially in T2WI. These MRI findings disappeared after central nervous symptom improvement in two of the three acute phase patients. However, we did not find a direct association between the MRI findings and the neuropsychology dysfunction. Image:41 years old female She had both legs motor nerve disorder. The cerebral microvascular lesions were found around the central sulcus in T2WI and DWI. It could be find only by using 7TeslaMRI. Image/graph: Conclusions: Cerebral microvascular lesions could be detected in patients with NPSLE by 7 Tesla MRI, suggesting that 7 Tesla MRI is a useful tool for diagnosing the cerebral lesions of NPSLE. It will be necessary to elucidate the association between cerebral microvascular lesions and neuropsychological dysfunction. Disclosure of Interest: None Declared